Assessing future energy and transport systems the case of fuel cells. - Pehnt, Martin (The International Journal of Life Cycle Assessment)
Goal, Scope and Background. Assessing future energy and transport systems is of major importance for providing timely information for decision makers. In the discussion of technology options, fuel cells are often portrayed as attractive options for power plants and automotive applications. However, when analysing these systems, the LCA analyst is confronted with methodological problems, particularly with data gaps and the requirement of an anticipation of future developments. This series of two papers aims at providing a methodological framework for assessing future energy and transport systems (Part 1) and applies this to the two major application areas of fuel cells (Part 2). Methods. To allow the LCA of future energy and transport systems forecasting tools like, amongst others, cost estimation methods and process simulation of systems are investigated with respect to the applicability in LCAs of future systems (Part 1). The manufacturing process of an SOFC stack is used as an illustration for the forecasting procedure. In Part 2, detailed LCAs of fuel cell power plants and power trains are carried out including fuel (hydrogen, methanol, gasoline, diesel and natural gas) and energy converter production. To compare it with competing technologies, internal combustion engines (automotive applications) and reciprocating engines, gas turbines and combined cycle plants (stationary applications) are analysed as well. Results and Discussion. Principally, the investigated forecasting methods are suitable for future energy system assessment. The selection of the best method depends on different factors such as required resources, quality of the results and flexibility. In particular, the time horizon of the investigation determines which forecasting tool may be applied. Environmentally relevant process steps exhibiting a significant time dependency shall always be investigated using different independent forecasting tools to ensure stability of the results. The results of the LCA (Part 2) underline that principally, fuel cells offer advantages in the impact categories which are typically dominated by pollutant emissions, such as acidification and eutrophication, whereas for global warming and primary energy demand, the situation depends on a set of parameters such as driving cycle and fuel economy ratio in mobile applications and thermal/total efficiencies in stationary applications. For the latter impact categories, the choice of the primary energy carrier for fuel production (renewable or fossil) dominates the impact reduction. With increasing efficiency and improving emission performance of the conventional systems, the competition regarding all impact categories in both mobile and stationary applications is getting even stronger. The production of the fuel cell system is of low overall significance in stationary applications, whereas in automotive applications, the production of the fuel cell power train and required materials lead to increased impacts compared to internal combustion engines and thus reduces the achievable environmental impact reduction. Recommendations and Perspectives. The rapid technological and energy economic development will bring further advances for both fuel cells and conventional energy converters. Therefore, LCAs at such an early stage of the market development can only be considered preliminary. It is an essential requirement to accompany the ongoing research and development with iterative LCAs, constantly pointing at environmental hot spots and bottlenecks.